Strain evolution of SiGe-on-insulator fabricated by germanium condensation method with over-oxidation. (December 2016) - Lin, Guangyang; Lan, Xiaoling; Chen, Ningli; Li, Cheng; Huang, Donglin; Chen, Songyan; Huang, Wei; Xu, Jianfang; Lai, Hongkai
Abstract: Strain evolutions of SiGe film during Ge condensation processes of SiGe on silicon-on-insulator were studied in detail with assistance of X-ray diffraction. At the beginning of Ge condensation, SiGe on silicon-on-insulator with low Ge fraction was oxidized at higher temperature of 1150 °C, the strong plastic deformation of buried SiO2 and Si-Ge intermixing relieved most of the strain in SiGe with increasing Ge fraction. When temperature was reduced to 900 °C for oxidation of SiGe layer with higher Ge fraction, Ge accumulation overmatched Si-Ge inter-diffusion, resulting in non-uniform profile of Ge in SiGe layer. During this period, plastic deformation of buried SiO2 can be neglected and dislocation gliding plays a significant role in relieving strain in SiGe, which enlarges the surface roughness. The strain in SiGe increases gradually with condensation time for the thickness of SiGe layer reduces close to its critical thickness, even with higher Ge fraction. Intensive over-oxidation of germanium-on-insulator materials was suggested to be effective to fully relax the compressive strain but should be precisely controlled to avoid surface deterioration.